Sight restoration reverses blindness-induced cross-modal functional connectivity changes between the visual and somatosensory cortex at rest - Nadvar, Negin; Stiles, Noelle; Choupan, Jeiran; Patel, Vivek; Ameri, Hossein; Shi, Yonggang; Liu, Zhongming; Jonides, John; Weiland, James (Frontiers in Neuroscience, 2022)
Resting-state functional connectivity (rsFC) has been used to assess the effect of vision loss on brain plasticity. With the emergence of vision restoration therapies, rsFC analysis provides a means to assess the functional changes following sight restoration. In our study, we show partial reversal of blindness-induced rsFC changes in Argus II retinal prosthesis patients, compared to those with severe retinitis pigmentosa (RP). For 10 healthy control (HC), 10 RP and 7 Argus II subjects, four runs of resting-state functional magnetic resonance imaging per subject were included in our study. rsFC maps were created with primary visual cortex (V1) as the seed. The rsFC group contrast maps for RP>HC, Argus II>RP and Argus II>HC revealed regions in post-central gyrus (PostCG) with significant reduction, significant enhancement, and no significant changes in rsFC to V1 for the 3 contrasts, respectively. These findings were also confirmed by the respective V1-PostCG ROI-ROI analyses between test groups. Finally, the extent of significant rsFC to V1 in PostCG region was 5961 in HC, 0 in RP and 842 mm3 in Argus II groups. Our results showed a reduction of visual-somatosensory rsFC following blindness consistent with previous findings. This connectivity was enhanced following sight recovery with Argus II, representing a reversal of changes in cross-modal functional plasticity as manifested during rest, despite the rudimentary vision obtained by Argus II patients. Future investigation with larger number of test subjects for this rare condition can further unveil the profound ability of our brain to reorganize in response to vision restoration.